Ghosts of the Shadow Market - Clare, Cassandra; Brennan, Sarah Rees; Johnson, Maureen 1973-; Link, Kelly; Wasserman, Robin (New York Margaret K. McElderry Books, 2019)
A collection of ten short stories, some of which were previously available online, that follow Jem Carstairs as he travels through the many Shadow Markets around the world, searching for a relic from his past.
Cast long shadows / by Cassandra Clare and Sarah Rees Brennan -- Every exquisite thing / by Cassandra Clare and Maureen Johnson -- Learn about loss / by Cassandra Clare and Kelly Link -- A deeper love / by Cassandra Clare and Maureen Johnson -- The wicked ones / by Cassandra Clare and Robin Wasserman -- Son of the dawn / by Cassandra Clare and Sarah Rees Brennan -- The land I lost / by Cassandra Clare and Sarah Rees Brennan -- Through blood, through fire / by Cassandra Clare and Robin Wasserman -- The lost world / by Cassandra Clare and Kelly Link -- Forever fallen / by Cassandra Clare and Sarah Rees Brennan.
Keywords: Paranormal fiction; Magic -- Juvenile fiction; Demonology -- Juvenile fiction; Vampires -- Juvenile fiction; Supernatural -- Fiction; Magic -- Fiction; Demonology -- Fiction; Vampires -- Fiction; Fantasy